Overview of Cognitive Function in the Elderly at Karya Kasih Resident Senior Medan City 2024 - Barus, Mardiati; Ginting, Friska Sri Handayani; Risda Siregar (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2025)
Introduction Cognitive function is a mental process used to acquire knowledge or abilities, including thinking,remembering, understanding, planning, and executing. The purpose of this study is to find out the description of cognitive function in the elderly in the senior resident of Karya Kasih Kota Medan. Methods This research is a descriptive research with a cross sectional approach. The population in this study is all elderly who are senior residents of the Medan City Head of Medan which totals 70 elderly with a sample of 41 elderly using purposive sampling techniques. The instrument used in this study is a standard MMSE questionnaire from the book Folstein & McHugh which was adopted by pelnelliti from the pelnellitian journal Dian Elka Putri (2021). The data analysis used in this study is univariate. Results the study showed that cognitive function in the elderly in the senior resident of Karya Kasih Kota Medan was in the dementia category of 34 people (82.9%). Conclusion is that in general, the elderly with dementia are more common than the elderly who experience normal cognitive function. It is hoped that the senior resident of Karya Kasih Kota Medan can provide activities to improve cognitive function in the elderly.